Permodelan Perilaku Daktail Balok T pada Beton Mutu Tinggi - Syaikhani, Ahmad; Tjitradi2, Darmansyah; Chairunnisa, Nursiah (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2025)
The use of reinforced concrete beams using a slender and high quality make manufacturing more efficient, but it could be a problem, especially in terms of deflection and torque occurs. Besides the issue of deflection and torsion of reinforced concrete beams are also vulnerable to shear failure, because the beam will suddenly fall without notice. By increasing the volume of concrete, it will increase the ability of beam bending, shear, ductility and strengthen the torsion beam, but if increasing the volume of concrete will increase the cost and increase the space or want a beam to beam slim in terms of aesthetics . This experiment without increasing the volume of concrete but do in the area of compressed concrete curbs and closed. Experimental models used are high quality concrete T beam with a length of 3.85 m . The number of flexural steel reinforcement 3 pieces with a diameter of 16 mm bending, body reinforcement of 8 mm diameter, 8 mm diameter tensile reinforcement and stirrups of 8 mm diameter (Ramaswamy, 2006). Furthermore, the implementation of a model created in ANSYS with the concrete material was modeled as SOLID 65, Steel material is modeled with SOLID 45, and reinforcing steel were modeled as LINK 8. Then redesign beam experiments with the same capacity so that the beam implementation in detail as reinforced concrete beams with a span length profiles T (L) 3.85 m, height (h) 350 mm, web beam width (bw) 150 mm, effective flens width (be) 375 mm, 450 mm and 600 mm. Beam profile T design used double the number of reinforcement rebars press 6 pieces of 10 mm diameter, reinforced pull 3 pieces of 22 mm diameter, and stirrups were used diameter of 10 mm. The quality of concrete used (fc') = 65 MPa. Flexural yield stress and tensile steel reinforcement is used (fy) = 400 MPa and reinforcement steel stirrups used (fy) = 240 MPa. Analysis of the modeling is done using the finite element method with a variation of the cross bar spacing of 50 mm, 75 mm, and 100 mm. The results showed that the load at the first crack that can be accepted on a concrete T beams with increasingly high quality meeting the local press stirrup spacing increased ( but less significant influence ). Then when the ultimate load on the beam can be accepted T on high strength concrete with closed the local press stirrup spacing increased ( significant influence ). Sengkang also affect the crack, the closer the distance stirrup in the press area will strengthen the concrete and reduce the widening cracks, as seen at the time of the first concrete crack and crack mangalami ultimate. While the effective width also affected, the greater the effective width of high strength concrete T beams will increase the moment capable of being held, so that the beam is getting stronger and greater ductility.